G39(P) Using mobile direct observation therapy to improve asthma inhaler technique. (May 2019) - Southey, C; Innes, S; Achakulwisut, V; Latham, S; Yap, E; Draper, A; Blamey, H; Gupta, A
Abstract : Introduction: Poor inhalation technique at home, even after repeated inhalation instructions in children with asthma is well recognised and Kamp et al reported only 30% asthmatics had adequate inhaler technique at home. This is a major factor in poorly controlled asthma, which increases risk of disease exacerbation, hospital admissions, and increased cost of care. Mobile Direct Observation Therapy (mDOT) is an innovative technology to monitor and improve inhaler technique at home. Aim(s)/objectives: We aimed to optimise inhaler technique at home and thereby improve asthma control in paediatric asthma patients. Methods mDOT installed on patients' smartphones enabled monitoring and assessment of asthma inhaler technique by asking patients to film themselves daily while using their inhaler. After 2 days baseline assessment, we emailed patients online educational videos to revise inhaler technique. After one week, we gave personalised daily feedback to patients via email or text on how their technique could be improved for 3 weeks. Results: We recruited 28 patients of which 6 patients (male:female, 1:1; mean age 7.5 years) completed the project. These patients had suboptimal baseline inhaler technique at home (72.83%), which increased to 83.33% with educational videos and 96.67% with daily feedback. Median Child Asthma Control Test (c-ACT) increased from 16.5 at baseline to 21 after 4 weeks. Median adherence to video submission was 59.05%. Discussion/conclusion mDOT with daily feedback shows potential in improving inhaler technique and asthma control, limited by the poor adherence to video submission. Other limitations were the small sample size and high dropout rate. Acknowledgements: We gratefully acknowledge the valuable input of Mr Richard Barbour for providing us with the Continga platform and all the patients with their families for their participation.